Insights into cell-to-cell and cell-to-blood-vessel communications in the brain: in vivo multiphoton microscopy - Osswald, Matthias; Winkler, Frank (Cell & tissue research, 2013)
A complex and reciprocal communication of cells with each other and with relevant parts of the tissue stroma governs many biological processes in both health and disease. However, in the past, the study of these anatomical and molecular interactions has suffered from a lack of appropriate experimental models. An imaging methodology aimed at changing this should allow intravital display and quantification in an intact non-traumatized organ, imaging over a wide range of time spans including extended periods (i.e., months), many repetitive measurements of the same cell or area to permit the study of the cause and consequence of biological processes, the display of various cell types and their reciprocal interaction with each other in three dimensions, the co-registration of relevant physiological parameters and reporters for selected molecular pathways and as high as possible resolution to visualize sub-cellular structures such as organelles. Remarkably, intravital multiphoton microscopy (in vivo MPLSM) through a chronic cranial window allows us to do all these things, making the brain the inner organ of choice for this technology. Here, we give an overview of the application of in vivo MPLSM to study the choreography of cellular, vascular and molecular interactions in the healthy brain and in neurological diseases. We focus on brain tumor formation, progression and response to therapies. This review further aims at demonstrating that we stand at the beginning of full exploitation of the opportunities provided by this technology and gives clues to future directions that appear most promising.
Gesehen am 09.12.2021